Complement Factor H Polymorphism in Age-Related Macular Degeneration - Narayanan, Raja; Butani, Virit; Boyer, David S.; Atilano, Shari R.; Resende, Gilberto P.; Kim, David S.; Chakrabarti, Subhabrata; Kuppermann, Baruch D.; Khatibi, Nikan; Chwa, Marilyn; Nesburn, Anthony B.; Kenney, M. Cristina (Ophthalmology (Rochester, Minn.), 2007)
To determine the association between complement factor H (CFH) polymorphism T1277C (tyrosine-402 → histidine-402) and phenotypic variations of age-related macular degeneration (AMD). Cross-sectional observational study. Subjects with dry or wet AMD and a control population consisting of age-matched non-AMD subjects from 2 clinical facilities examined during the period January 1, 1999 through December 31, 2002. Total DNA isolated from the leukocytes of 66 AMD subjects and 58 age-matched control subjects was studied. The CFH gene was amplified by polymerase chain reaction and analyzed by Nla III restriction fragment length analysis. Incidence of CHF polymorphism with the occurrence of AMD. Among the AMD patients, 15 had dry and 51 had wet AMD. For the CFH gene, the T1277C variant showed the genotype distribution as CC, TC, and TT. There was a strong association between homozygous C and AMD compared with the control population (odds ratio [OR] = 3.4; 95% confidence interval [CI], 1.32–8.74; P = 0.0053). Furthermore, dry AMD had a stronger association (OR, 8.32; 95% CI, 2.30–30.11; P = 0.001) than wet AMD (OR, 2.49; 95% CI, 0.90–6.84; P = 0.039) compared with the control population. Homozygous T was more prevalent in the control subjects compared with AMD patients (OR, 5; 95% CI, 2.18–11.43; P = 0.00005). Complement factor H polymorphism T1277C (tyrosine-402 → histidine-402) is strongly associated with both dry and wet AMD and points to a possible role for inflammation in the pathogenesis of AMD.